Leaching of lead from sphalerite concentrate direct leaching residue by hydrochloric acid and sodium chloride for preparation of lead oxides - Fan Y.-Y.; Liu Y.; Niu L.-P.; Jing T.; Zhang T.-A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The purpose of this study was to select and propose an applicable method for extracting lead from sphalerite concentrate direct leaching residue. A large number of experiments were conducted to extract lead from sphalerite concentrate direct leaching residue by hydrochloric acid and sodium chloride solution as leachates. The main optimum parameters were determined, such as a liquid-solid ratio of 17.5-1, a reaction temperature of 85°C, an initial hydrochloric acid concentration of 1.3 mol/L, an initial sodium chloride concentration of 300 g/L, and a reaction time of 60 min. Ninety-five percent of the zinc, 96.0% of the iron, and 93.7% of the lead were extracted into leachate at the optimum conditions. The lead in the leachate was in the form of [PbCl4]2-. After the leachate was purified to remove impurities, it was converted into lead oxalate by sodium oxalate as a precipitant. Finally, lead oxalate was decomposed to obtain lead oxide powders via a high-temperature calcination process.